A critical review of smart hospitality and tourism research. Issue 2 (24th November 2021) - Law, Rob; Ye, Huiyue; Chan, Irene Cheng Chu
Abstract : Purpose: This study aims to build a comprehensive knowledge structure of smart hospitality and tourism research. Design/methodology/approach: Content analysis is carried out on the themes of pertinent research from the perspectives of customers, suppliers, technology and policymakers. Findings: Results show that over half of the reviewed articles are carried out from the perspective of customers, while those of suppliers, technology and policymakers are less discussed. The unbalanced number of articles reveals an evident mismatch between the supply and demand. Practical implications: Findings provide theoretical and practical implications from different perspectives. Collaboration among various stakeholders is also advocated to achieve sustainable and balanced development of the smart hospitality and tourism industry. Originality/value: This study contributes to smart hospitality and tourism research through an in-depth review of relevant literature. Based on the findings, the identified research gaps provide potential directions for future knowledge development.